2014
DOI: 10.1177/1475090213506183
|View full text |Cite
|
Sign up to set email alerts
|

Structural reliability assessment of container ship at the time of accident

Abstract: Hull girder reliability assessment of the MSC Napoli at the time of accident is presented. Loads considered in the study are still water bending moments, vertical wave bending moments and whipping bending moments, while structural capacity is represented by the hull girder ultimate strength. Load combination between wave and whipping bending moments is considered. The probability of failure is calculated using a first-order reliability method. Sensitivity study is performed in order to investigate influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As an example, for structural reliability analysis, Downes and Pu 58 proposed a methodology for assessment of ship hull girder ultimate strength reliability to improve the ship design from the perspective of safety. Additionally, the study conducted by Parunov et al, 59 on a hull girder reliability assessment of the MSC Napoli at the time of its accident can be given as another example. To calculate the probability of failure, a first-order reliability method was used in the study.…”
Section: Can Be Givenmentioning
confidence: 99%
“…As an example, for structural reliability analysis, Downes and Pu 58 proposed a methodology for assessment of ship hull girder ultimate strength reliability to improve the ship design from the perspective of safety. Additionally, the study conducted by Parunov et al, 59 on a hull girder reliability assessment of the MSC Napoli at the time of its accident can be given as another example. To calculate the probability of failure, a first-order reliability method was used in the study.…”
Section: Can Be Givenmentioning
confidence: 99%
“…Although whipping certainly occurred at the time of the accident, it is still not clear how much it actually contributed to the hull girder failure (Storhaug, 2009). Parunov et al (2014), in their investigations of the MSC Napoli, proposed the structural reliability approach, which enables identification of the relative importance of various pertinent variables on the structural failure. Sensitivity analysis, which is regular part of the structural reliability study, showed that the most important random variable at the time of the accident appears to be the modelling uncertainty in the bending capacity (32%).…”
Section: Load Uncertaintiesmentioning
confidence: 99%